2020
DOI: 10.1016/j.pbi.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Ento(o)mics: the intersection of ‘omic’ approaches to decipher plant defense against sap-sucking insect pests

Abstract: Plants are constantly challenged by insect pests that can dramatically decrease yields. Insects with piercing-sucking mouthparts, for example, aphids, whiteflies, and leaf hoppers, seemingly cause less physical damage to tissues, however, they feed on the plant's sap by piercing plant tissue and extracting plant fluids, thereby transmitting several plantpathogenic viruses as well. As a counter-defense, plants activate an array of dynamic defense machineries against insect pests including the rapid reprogrammin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 76 publications
1
28
0
1
Order By: Relevance
“…In addition of JA, SA is involved in plant defense signaling and provides resistance to phloem-feeding insects [4,8,55]. Our previous work and the data presented in this work are in agreement that the CLA feeding on Mp708 plants significantly induced the expression of genes involved in SA biosynthesis, however, pharmacological studies confirmed that mir1-dependent defense against CLA is disengaged from SA pathway [13].…”
Section: Modulation Of Genes Involved In Phytohormonal Pathways Beforsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition of JA, SA is involved in plant defense signaling and provides resistance to phloem-feeding insects [4,8,55]. Our previous work and the data presented in this work are in agreement that the CLA feeding on Mp708 plants significantly induced the expression of genes involved in SA biosynthesis, however, pharmacological studies confirmed that mir1-dependent defense against CLA is disengaged from SA pathway [13].…”
Section: Modulation Of Genes Involved In Phytohormonal Pathways Beforsupporting
confidence: 90%
“…Phytohormones play a key role in modulating plant defense against sap-sucking aphids [3,4,8,49]. Here, we investigated the transcriptomic response of the genes involved in phytohormone biosynthesis in response to CLA infestation in the resistant and susceptible genotypes.…”
Section: Modulation Of Genes Involved In Phytohormonal Pathways Beformentioning
confidence: 99%
See 1 more Smart Citation
“…Insects may overcome this by secreting effectors in salivary proteins or capitalizing SMs (Lu et al 2018). Although the strategies used by plants to defend against each kind of insect may vary (Harun-Or-Rashid et al 2018), common mechanisms involve JA signaling, detoxification, cell wall modifications, photosynthesis, phytohormones, and defensive SMs (for review, see Ling et al 2019;Zogli et al 2020).…”
Section: Response Of Rice To Insectsmentioning
confidence: 99%
“…Several omics strategies alone or in combination have been used to evaluate plant-aphid, and plant-insect interactions [for example: (Wu and Baldwin, 2010;Maag et al, 2015b;Tzin et al, 2015;Zhou et al, 2015;Wozniak et al, 2017;Kiani and Szczepaniec, 2018;Erb and Reymond, 2019;Nalam et al, 2019;Sanchez-Arcos et al, 2019;He et al, 2020;Zhang et al, 2020;Zogli et al, 2020)]. In general, these studies have shown extensive changes in the transcriptomes and metabolomes upon insect herbivory.…”
Section: Introductionmentioning
confidence: 99%